ANTI-PYRETIC ACTION OF Caulerpa lentillifera, Hibiscus rosa-sinensis AND Piper sarmentosum AQUEOUS EXTRACT IN MICE - Daud, Dzulsuhaimi; Mohd Arsad, Nur Fazuliana; Ismail, Asmida; Tawang, Alene (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present study was conducted to evaluate the anti-pyretic activity of Caulerpa lentillifera, Hibiscus rosa-sinensis, and Piper sarmentosum aqueous extracts. Methods: The suspension of yeast was injected intraperitoneally (0.1 g/kg of bodyweight [BWT]) to induce fever in experimental animals. Rectal temperature was recorded every hour with a lubricated digital thermometer and animals with at least 0.7Â°C elevations in body core temperature were included in the experiment. The animals with fever were administered orally with aqueous extracts of C. lentillifera, H. rosa-sinensis, and P. sarmentosum (500 mg/kg of BWT). Another group was given the commercial drug, acetaminophen (10 mg/kg of BWT), to serve as a control. Results: The result of the study showed that C. lentillifera and H. rosa-sinensis aqueous extracts significantly (p<0.05) effective in combating fever. However, P. sarmentosum aqueous extract has no potential as an anti-pyretic agent. Conclusion: H. rosa-sinensis and C. lentillifera aqueous extracts have anti-pyretic potential but not P. sarmentosum aqueous extract. Keywords: Caulerpa lentillifera, Hibiscus rosa-sinensis, Piper sarmentosum, Anti-pyretic, Fever, Pyrexia, Yeast.